Understanding disaster risk for advancing resilient development knowledge note. - Roy, Arghya Sinha (Metro Manila, Philippines Asian Development Bank, 2018)
This knowledge note highlights ten key considerations for enhancing understanding of disaster risk among public investment planners.This publication is designed to aid engagement of public investment planners in the disaster risk assessment process. If the sustainable development goals are to be achieved, it is necessary to integrate disaster risk consideration in the public investment planning processes. Government officials involved in public investment planning have a key role to play in defining the risk information related needs and supporting the development of such information in close partnership with hydro meteorological and geological institutes and relevant national agencies that address disaster risk management and climate change adaptation.
Keywords: Climatic changes -- Risk management; Emergency management; Electronic books